Kenyan and British social imaginaries on Julie Ward's death in Kenya - Musila, Grace Ahingula (My University, 2009)
Abstract The study explores the narratives on the 1988 death of 28 year old British tourist, Julie Ann Ward in Kenya's Maasai Mara Game Reserve. Julie Ward's death in Kenya attracted widespread attention in Kenya and Britain culminating in at least three true crime books, significant media coverage and rumours in Kenya. The study reflects on the narratives on Julie Ward's death, with particular interest in the discourses that gained expression through, or were inscribed, on Julie Ward's death and the quest for her killers. The study is also interested in the ways in which the Julie Ward case and the discourses it inspired offer a critique of rationality, and the accompanying unity of the subject, expressed through a logocentric impulse as key tenets of a Western modernity that continues to mediate metropolitan readings of postcolonial Africa. The study reveals that Julie Ward's death traversed various discursive sites, which were laden with specific ideas on race, gender, the postcolonial African state, Western modernity, female sexuality and black male sexuality, among a host of other issues; all of which tinted British and Kenyan narratives on the circumstances surrounding the death. The study argues that the authors of the three books on the Ward tragedy rely on colonial archives on Africa, and actively mobilize notions such as the myth of the uncontrollable black male libido and its threat to the vulnerable white woman in understanding the Ward tragedy. While these writers cling to these notions of the black peril, the noble savages, Africa as the tourist's wildlife paradise, and the dysfunctional postcolonial state; Kenyan publics read the murder as another symptom of a criminal political elite's brutal deployment of violence to secure immunity for its criminal activities.However, the two sets of ideas are largely disarticulated, and as the study reveals, the British stakeholders in the case are blinded by a rigid polarization of Kenya and Britain, which presumes a superior British moral and technological integrity. These assumptions blind the Ward family to British complicity in the cover up of the truth in Julie Ward's murder; while at the same time, rendering them illiterate in the local textualities which remain inaccessible to the instruments of Western modernity that are privileged in the quest for truth and justice in the Julie Ward murder. Julie Ward’s presence in Kenya, her death and the subsequent quest for her killers is consistently haunted by neat dichotomies, derived from various masternarratives. The study traces these dichotomies, in a bid to outline their configurations and the outcomes of their deployment, while consistently keeping the grey areas of entanglements between these dichotomies in sight. It is in these grey areas that we see the contradictions, blindspots, critiques, complicities and forms of agency that were at play just under the radar of these neat polarities. From these grey terrains, we catch glimpses of the workings of these dichotomies as discursive masks which conceal the faultlines that rend the masternarratives. The study finds that in many ways, Julie Ward's death in Kenya may be positioned in a transitional space between colonial whiteness and an emergent postcolonial whiteness, which betrays heavy imprints of the grammars of colonial whiteness, including the messianic white male authority, wildlife tourism and conservation. To this end, the study suggests, one of the factors that hampers the quest for truth and justice in the Ward case is the failure to forge viable grammars of whiteness in the postcolonial context. Such viable grammars would be able to access local textualities and retain an awareness of the underlying complicities and faultlines that now rig colonial Manichean binaries, which are largely mediated by the interests of capital. The novel The Constant Gardener and the film Ivory Hunters (1989) - both of which make implicit allusions to the Julie Ward case – eloquently articulate these complicities and faultlines.
Keywords: Julie Ward; Modernity; Social imaginaries; Narrative